Immediate Effects of Cervical Thrust Manipulation in Weightbearing and Non-weight bearing on Cervical Range of Motion in Asymptomatic Individuals – A Randomized Clinical Trial (International Journal of Physiotherapy, 2021)
Background: Thrust manipulation of the cervical spine has improved the range of motion (ROM). Hence, the study evaluated the effects of cervical thrust manipulation in weight-bearing (CTM-WB) and non-weight-bearing (CTMNWB) on the cervical ROM (CROM) in asymptomatic individuals.Methods: A randomized clinical trial was conducted on 74 asymptomatic subjects among 18 – 30 years who had reduced neck ROM. Participants were assessed for CROM using the digital goniometer at the baseline and immediately after the intervention, i.e., within 5 minutes post-intervention. They were randomized into two groups using the envelope method. Participants were given cervical manipulation in weight-bearing or non-weight-bearing positions based on their respective group allocation. The data were analyzed using the paired t-test and the unpaired t-test.Results: Statistical analysis revealed significant differences in pre and post-values of all the degrees of freedom in CTMWB (p < 0.05) and CTM-NWB (p < 0.05) groups.Conclusion: CTM-WB and CTM-NWB positions are both effective in improving CROM. Hence CTM-WB can also be used during clinical practice, especially in individuals who have difficulty lying in a supine position. Since manual therapy techniques are known to correct positional faults, the two cervical manipulation techniques' effects can be studied on individuals with forward head posture or parameters such as pain and disability.